Katedra Piotra w nauczaniu Optata z Milewy jako ostateczny probierz prawdziwości Kościoła - Koczwara, Stanisław (Vox Patrum, 2004)
The article St. Peter’s Chair in the Teaching of Optatus of Mileve as the Final Criterion of Authenticity of the Church is particularly about certain period in the catholic Church history in IV century, which was experienced in the Latin Africa by schism of the Donatists. In order to prevent the division Saint Optatus broadcasted the extremely mature conception of the Saint Peter's chair, that was based on Saint Cyprian's idea. Optatus describes this power/chair as a first gift for the Church - meaning Saint Peter, who is a source of the rest of gifts such as baptism and penance. This chair was transmitted to the Saint Peter's successors as a source and tool for the Church union. Everyone who wanted to be in the harmony with me Church should maintain complete union with bishop of Rome.